The ethical and legal duty to prevent and reduce to the maximum the appearance of new disabilities of the elderly in Chile - Riveros Ferrada, Carolina; Barcia Lehmann, Rodrigo (Acta Bioethica, 2015)
In this article we pretend to show the inconsistency between the recent Law 20.584 with the United Nations Convention about the Rights of Persons with Disabilities. Such persons, in certain stage of their disease, would not be able to participate in research because of their disability condition. We consider that this impossibility does not agree with article 25 of the Convention, which requires the States prevent and reduce to the maximum the appearance of new disabilities, included those that initiate in the elderly. The problem generated does not have only a legal perspective, but also produces an ethical conflict affecting the State, health care professionals, patients and their families. For this reason, we propose a harmonic and systematic interpretation of article 28 of Law 20.584 with the Convention, incorporating ethical elements necessary for this interpretation.